2007
DOI: 10.1093/jn/137.4.1119
|View full text |Cite
|
Sign up to set email alerts
|

Meat Supplementation Improves Growth, Cognitive, and Behavioral Outcomes in Kenyan Children1,

Abstract: A randomized, controlled school feeding study was conducted in rural Embu District, Kenya to test for a causal link between animal-source food intake and changes in micronutrient nutrition and growth, cognitive, and behavioral outcomes. Twelve primary schools were randomly assigned to 1 of 4 groups. Children in Standard I classes received the local plant-based dish githeri as a midmorning school snack supplemented with meat, milk, or fat added to equalize energy content in all feedings. The Control children re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
4
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 16 publications
8
154
4
6
Order By: Relevance
“…Primarily, school-feeding programmes have been established to address hunger and its negative effect on the nutritional status and learning capacity of school-age children (WFP, 2015). Although, the provision of school meals to SAC cannot reverse all damage caused by early nutritional deficits (Bundy, 2009), many studies have reported nutritional and health benefits of school feeding programmes (Afridi, 2010;Ahmed, 2004;Arsenault et al, 2009;Musamali, 2007;Neervoort et al, 2013;Neumann, Murphy, Gewa, Grillenberger, & Bwibo, 2007;Zeba, Martin Prevel, Some, & Delisle, 2006). A systematic review of school-feeding programmes have reported improvements in weight, height in younger children (6-8 years), school attendance, mathematics performance, bone mineral density, arm muscle, concentrations of B -vitamins and behaviour among participants (Kristjansson et al, 2007).…”
mentioning
confidence: 99%
“…Primarily, school-feeding programmes have been established to address hunger and its negative effect on the nutritional status and learning capacity of school-age children (WFP, 2015). Although, the provision of school meals to SAC cannot reverse all damage caused by early nutritional deficits (Bundy, 2009), many studies have reported nutritional and health benefits of school feeding programmes (Afridi, 2010;Ahmed, 2004;Arsenault et al, 2009;Musamali, 2007;Neervoort et al, 2013;Neumann, Murphy, Gewa, Grillenberger, & Bwibo, 2007;Zeba, Martin Prevel, Some, & Delisle, 2006). A systematic review of school-feeding programmes have reported improvements in weight, height in younger children (6-8 years), school attendance, mathematics performance, bone mineral density, arm muscle, concentrations of B -vitamins and behaviour among participants (Kristjansson et al, 2007).…”
mentioning
confidence: 99%
“…Study participants were not blinded to the group feeding assignment, but they were blinded to study hypotheses, as were teachers and field staff. This is the first cluster randomized, controlled feeding intervention study to analyse the contribution of the addition of ASF, particularly meat, on morbidity outcomes in addition to the previously demonstrated cognitive, behavioural and body composition improvements (47,63) . An unexpected and important outcome was the positive impact of the addition of a considerable amount of retinol to the Plain Githeri snacks, which demonstrated the value of such fortification in reducing morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…So Neumann began a trial in Kenya 3 . Her team selected 12 schools with children aged 6 to 14, and gave some of the children midmorning snacks.…”
Section: Meat For the Poormentioning
confidence: 99%